A study on the level of awareness of Islamic Unit Trust in Terengganu / Azian Abd Ghani … [et al.] - Abd Ghani, Azian; Alias, Muhazita; Zakaria, Zainuddin; Abu Bakar, Kalsom (Research Management Institute (RMI), 2008)
The purpose of this study was to identify the level of awareness on Islamic Unit Trust funds in Terengganu. The respondents selected were academicians in the state of Terengganu higher learning institutions. The state of Terengganu that has 95% Malay (Muslims) population still registered the lowest number of unit trust investors. This was proven that out of 315 respondents surveyed from seven (7) higher learning institutes, only 71 (22.5%) of them invested in the Islamic Unit Trust funds. The balance has not yet invested, although 184 (75.4%) of the non-investors were aware of the existence of this product. Interesting to note that out of those who invested only 36 respondents knew on the mechanism of how the Islamic Unit Trust were operated, 35 respondents did not know. Despite lack of understanding on the Islamic Unit Trust funds mechanism, 61% were satisfied with their investment and has the intention to increase their investment in the future. Those aged 25 to 40 years, married with a higher disposable income were the representation of investor's demographic profile. The major factors that influenced their investment decision were the syariah based operation, followed by the investment security and low risk involvement. Internet and investment seminars were two major sources of information that educated those who invested and understood the scheme. It is important that the investment managers disseminated their information via integrated marketing communication campaigns on products and promotional efforts. This can be done by educating their investors and potential investors using internet, investment seminars, Islamic unit trust week, well-trained unit trust financial advisors beside advertising and promoting their products through printed and electronic media. The researchers recommended three strategies targeted to three major groups of investors. First strategy was to continue their marketing relationship program to the current investors. Second strategy was to familiarize the Islamic Unit Trust potential investors with product features, and how it can benefit them functionally, symbolically and experientially. Finally, the third strategy was to target unaware potential investors by using the 2 in 1 strategy i.e. aware and attract them to invest.